Reconstruction of historical precipitation (1877-2014) for the southwest of the Sierra Gorda Biosphere Reserve, Querétaro, Mexico - Mendoza-Villa, Omar N.; Cambrón-Sandoval, Víctor Hugo; Cerano-Paredes, Julián; Cervantes-Martínez, Rosalinda; Soto-Correa, José C. (Revista Chapingo Serie Ciencias Forestales y del Ambiente, 2018)
Introduction: Historical analysis of climate variability represents a first approach to know the recurrence of events such as droughts and floods, as well as to infer possible climate trends. This study is the first historical analysis in the Sierra Gorda Biosphere Reserve (SGBR). Objectives: To develop dendrochronological series with the ring width of Pinus greggii Engelm. ex Parl. and P. montezumae Lamb., determine their potential to reconstruct rainfall variability, and reconstruct, minimally, precipitation variability and its relationship with the El Niño Southern Oscillation (ENSO) for the last century. Materials and methods: In the southwest of the SGBR, 87 samples were extracted from 29 trees, of which 15 (45 rays) corresponded to P. greggii and 14 (42 rays) to P. montezumae. The growths were dated using dendrochronological techniques. Results and discussion: The generated chronology, composed of 138 years (1877-2014), was significantly correlated (P < 0.01) with the January-May rainfall. The reconstruction of the winter- spring seasonal precipitation variability indicates that there is interannual and interdecadal variation. Four severe droughts were identified (1887, 1951-1956, 1969-1972 and 2012) and two periods with excellent precipitation (1962-1967 and 1983-1993). The severest droughts in the southwest of the SGBR synchronize with extreme events reconstructed for the north of the country with a 50-year recurrence interval. Conclusion: Pinus greggii and P. montezumae responded significantly to the precipitation of the winter-spring period, which allowed the reconstruction of rainfall variability over a period of 138 years. Variability has been significantly modulated by ENSO.